Contribuições da história de vida da cientista brasileira Bertha Lutz para o ensino de ciências - Cordeiro, Thamires Luana (2022)
Bertha Lutz was a Brazilian scientist, feminist, educator and politician who learned to study feminist life about the amphibian group. She was responsible for guaranteeing a series of civil and political rights for Brazilian women, among them, what gained more prominence was the right to vote for women conquered in 1932. In the field of Science, Bertha Lutz stood out in the area of zoology describing and cataloging species of anuran amphibians and publishing important studies on this group of animals. Through studies presented in the context of this research, gaps were identified with regard to pedagogical practices in the school context on Women in Science on Amphibian Teaching in the Early Years. Therefore, it is necessary to invest in didactic strategies that aim to fill these gaps in the school environment. Thus, TD didactics were carried out on the biography of a Didactic Sequence and it was carried out in the biography (it was a History of a Didactic Sequence and in science studies. The Didactic Sequence was organized in five moments, being a preliminary activity and four stages of Thus, it was discovered a year ago with students from the 3rd of Elementary School of a municipal school in Santa Maria - RS, in which it sought to investigate the conceptions about the application of the theme and later to publish the importance of the group of Anuran Amphibians and the The role of Women in Science In general, we identified the need for further study on the subject of this study through Science Teaching so that I - children understand that Science is human and historical production, II - that Women also were and are part of the History of Science and III - the importance of preserving and respecting the group of anuran Amphibians. From this study, it was possible to perceive that from the application of the SD, the children were sensitized in some way, as changes in perceptions were identified during the application process, such as, for example, the children mentioned the name of Bertha Lutz and of inventions carried out. by women during research stages when they are already familiar with the topic. The initial feeling of fear and disgust towards anuran amphibians disappeared as children began to understand the importance of this group of animals. However, he noticed that the image of Science was often associated with a male scientist, wearing a lab coat and carrying out experiments inside a laboratory. In this way, this research signals the need for discussions on the History of Science since the Early Years of Elementary School so that children know how to value Science as a human production also carried out by women in different places, times and areas of study. Therefore, from this study it was possible to divulge the story of a woman scientist and at the same time to propose didactic activities that sought to present the importance of the role of Women in Science and the group of Anuran Amphibians for the environment through the history of life and the studies by Bertha Lutz. Thus, it is concluded that, even if indirectly, Bertha Lutz made important contributions to Science Teaching possible.